Dispersão e controle de antracnose em feijão - Cerbaro, Lilian (2013)
Beans (Phaseolusvulgaris) are ones of the most consumed foods in Brazil, about 17 kg/habitant/year. Our country is the most world productor with 20% of total production. The beans cultive is limitated by some diseases, among them, the anthracnose, caused by fungus Colletotrichumlindemuthianum. The disease is favored by frequently rains, it can results in looses of until 90%. Internally in the farming, the pathogen is scattered by splash of rain or irrigation. This process can be influenced by the proximity of plants, determined by its arrangement. In this research, it was used seeds of cultives susceptible to anthracnose, spread in field to evaluate the chemical control of anthracnose in both cultives with habit of growing sympodial (Carioca) and monopodial (Dark Pearl), and both populations of plants (205.000 and 253.000/ha). It was used fungicides fentin hydroxide + azoxystrobin (mertin + amistar, carbendazin + azoxystrobin (derosal + amistar) and trifloxystrobin + tebuconazole (native), and both applies (pre-flowering and 20 days after). It was evaluated also the progress of disease, from focus plants (inoculated in house of vegetation), in far plants 0,5 m; 1 m; 1,5 m; 2 m; 2,5 m and 3 m, with and without irrigation by sprinkling. The influence of simulated rains also was tested about the occurrence of anthracnose, in volumes of 2, 4, 8, 16, 32 and 64 mm, as the interference of silicon adjuvant polietersiloxano (Break Thru) applied 4 h before the rains simulation. At the end, it was estimated a CI 50 (necessary concentration to inhibit the growing of fungus in 50%) of some active ingredients to pathogen: pyraclostrobin (comet), pyraclostrobin + fluxapyroxad (BAS 703), pyraclostrobin + epoxyconazol + fluxapyroxad (BAS 702), azoxystrobin (priori), azoxystrobin + difenoconazol (amistar top), difenoconazol(score) and clorotalonil (bravonil) compared to standard fentrin hydroxide (mertin). It was used the method of inhibit of mycelial growing among culture of BDA supplemented with 0; 0,01; 0,1; 1; 5 and 10 mg/L. The chemical control presented similar results, independently of the cultive and the population. The biggest severity was observed in plants positioned to 0,5 m of distance, reaching 12,25% in the condition with irrigation and 0,75% in the not irrigated area. When the distance of source of inoculum increased, the final severity with irrigation decreased to 6,25% (1,0 m), 5,00% (1,5 m), 4,00% (2,0 m), 3,75% (2,5 m) and 2,25% (3,0 m). It was observed that with 1 mm of rain it was just possible visualize the symptoms of disease, which increased until the volume of 32 mm. In plants with adjuvant, the symptoms were detected after 8 mm of rain. The proportion of final severity varied from 0,03 with adjuvant to 0,23 less the product. The values of CI 50 were smaller to fungicides based on strobilurin and strobilurin + carboxamide, that show, thus, potencial to substitution of fentin hydroxide